Sinergi Halal Center UMKU dan PMKM Prima Indonesia Dalam Mendorong Produk UMKM Bersertifikat Halal - Mu'adzah, Muadzah; Ridwanto, Muhammad; Rosnarita, Intan Adevia; Masithoh, Anny Rosiana; Astuti, Amy Arbaatun Nisa (LPPM UMRI, 2026)
The rapid competition in business and consumer demands in purchasing Halal and Thayyib products are the basis for the importance of MSME products having halal certificates and labels. This community service program aims to socialize halal policies, halal product processes and verification of halal product processes, until MSMEs have halal certificates. The community service method with pre-service namely problem identification, socialization and post-service with facilitation of MSME halal certification until the certificate is issued. By holding this community service, participants gain motivation and understanding in applying for halal certification until they have halal certificates and halal labels for their products.